2010
DOI: 10.1002/acr.20117
|View full text |Cite
|
Sign up to set email alerts
|

Functional impairment of the arterial wall in primary Sjögren's syndrome: Combined action of immunologic and inflammatory factors

Abstract: Objective. Primary Sjö gren's syndrome (SS) shares clinical and serologic features with rheumatoid arthritis and systemic lupus erythematosus, 2 diseases characterized by acceleration of atherosclerosis. Signs of precocious atherosclerosis have also been shown in SS, although the pathogenic basis of early arterial damage is unclear. The arterial wall was functionally evaluated in SS subjects with analysis of the role played by disease-related factors. Methods. Endothelium-dependent flow-mediated vasodilation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
60
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 41 publications
8
60
3
Order By: Relevance
“…This finding apparently contrasts with Gerli et al, who observed a significant reduction in nitrate-mediated vasodilatation in women with primary SS with anti-SSB (10). Nonetheless, these authors did not find an association between anti-SSB and the presence of endothelial dysfunction evaluated by means of flow-mediated vasodilatation (10) or with CIMT (9), although in this latter study an association with anti-SSA was found. These conflicting results may be due in part to differences in patient characteristics and in the methods used for evaluating subclinical atherosclerosis, suggesting that they measure different phenotypes of atherosclerosis.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…This finding apparently contrasts with Gerli et al, who observed a significant reduction in nitrate-mediated vasodilatation in women with primary SS with anti-SSB (10). Nonetheless, these authors did not find an association between anti-SSB and the presence of endothelial dysfunction evaluated by means of flow-mediated vasodilatation (10) or with CIMT (9), although in this latter study an association with anti-SSA was found. These conflicting results may be due in part to differences in patient characteristics and in the methods used for evaluating subclinical atherosclerosis, suggesting that they measure different phenotypes of atherosclerosis.…”
Section: Discussioncontrasting
confidence: 44%
“…The size of the cohort was relatively small, and some statistical significance between subgroups was probably not reached because of a lack of statistical power. However, our study (44 patients and 78 controls) along with the study by Gerli et al (45 patients and 59 controls) (10) are the largest studies (cross-sectional) published to date. Conversely, all of our patients had anti-Ro/SSA, which contrasts with larger cohorts in which the prevalence of this antibody ranged from 50% (35) to 90% (6).…”
Section: Discussionmentioning
confidence: 71%
“…Low HDL cholesterol levels was a constant finding among SS patients in several studies (Vaudo, Bocci et al 2005;Lodde, Sankar et al 2006;Gerli, Vaudo et al 2010). Of interest, HDL along with total cholesterol were found to be associated with immunoglobulin G levels.…”
Section: Ssmentioning
confidence: 97%
“…Of interest, in the younger age group (<40y), hypertension was also associated with higher non obesity-related insulin levels, while in the older group (>40y), with age and obesity (Sabio, Vargas-Hitos et al 2011). Arterial hypertension did not seem to influence subclinical atherosclerotic disease in patients with pSS (Vaudo, Bocci et al 2005;Rachapalli, Kiely et al 2009;Gerli, Vaudo et al 2010). …”
Section: Slementioning
confidence: 99%
See 1 more Smart Citation